2015
DOI: 10.1128/microbiolspec.mb-0016-2014
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies for Studying Biofilms

Abstract: Bacteria have traditionally been studied as single-cell organisms. In laboratory settings, aerobic bacteria are usually cultured in aerated flasks, where the cells are considered essentially homogenous. However, in many natural environments, bacteria and other microorganisms grow in mixed communities, often associated with surfaces. Biofilms are comprised of surface-associated microorganisms, their extracellular matrix material, and environmental chemicals that have adsorbed to the bacteria or their matrix mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 264 publications
(227 reference statements)
0
58
0
1
Order By: Relevance
“…The majority of studies are about induction of larval settlement by bacteria. The new omic techniques-such as metagenomics, metabolomics, proteomics, and transcriptomics-allow to characterize microbes in biofilms, identifying metabolites produced and genes responsible for their production [11][12][13][14]86]. In the future, the development of such techniques and the lower cost of such methods will result in an increase of molecular studies of microbe-larva interactions.…”
Section: Future Studiesmentioning
confidence: 99%
“…The majority of studies are about induction of larval settlement by bacteria. The new omic techniques-such as metagenomics, metabolomics, proteomics, and transcriptomics-allow to characterize microbes in biofilms, identifying metabolites produced and genes responsible for their production [11][12][13][14]86]. In the future, the development of such techniques and the lower cost of such methods will result in an increase of molecular studies of microbe-larva interactions.…”
Section: Future Studiesmentioning
confidence: 99%
“…25 Researchers have used an in vitro periodontitisassociated dental biofilm model for evaluating the antimicrobial effects of various treatment options for peri-implant disease because in vivo periodontitisassociated biofilm can be altered by host problems and many ethical considerations. 26 Frankline et al 27 suggested that an in vitro dental biofilm model using a Center for Disease Control and Prevention (CDC) biofilm reactor (dynamic method) can create an environment similar to the saliva and gingival crevicular fluid in the oral cavity. However, few studies have reported the efficacy of an LED toothbrush on dental biofilm attached to a zirconia surface by CDC biofilm reactor.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Kim et al have found that fluid flow represses the internal signaling (quorum sensing) of S. aureus, which can be associated with the elution of signaling molecules [114,115]. Nevertheless, several methods based on continuous flow have been introduced [116,117].…”
Section: Flow Systemsmentioning
confidence: 99%